Traffic Flow Modeling of University Road Peshawar Using Simulation - Ibrahim, Muhammad Mustafa; Khan, Kamran; Atiq, Rabia (International Journal of Scientific Research in Computer Science and Engineering, 2023)
The city of Peshawar is facing a severe traffic problem due to the rapid increase in population and the inefficient public transport system. This study focuses on analyzing the main reasons for traffic congestion in Peshawar and proposes a solution through traffic simulation modeling. The lack of traffic signals, narrow roads, and lack of awareness about traffic laws contribute to the traffic jams. The study aims to develop a PTV VISSIM traffic simulation model and improve the transportation system to improve the traffic congestion problem. Data collection is conducted at different locations and times, including vehicle speed, types, and length. The findings will provide insights for better traffic management and infrastructure planning in Peshawar.